(untitled) (Journal of Mathematics Mechanics and Computer Science, 2025)
As a result of solving certain tasks, new digital data and knowledge appear, that is, systematized factual or tested messages. They are generalized as a set of laws, theories and other ideas and views. Later, this knowledge is part of the digital data needed to solve other tasks or clarify the previous one. In the past five years, the number of participants in the web-based cyber system has increased dramatically, but cyber security in cyberspace and security on the Internet have become increasingly difficult for Internet users and service providers. A functioning table-based authentication modeling is proposed to protect personal and confidential information of cyber system participants and networks in cyberspace from unauthorized access and to ensure cyber security. Social engineering and low complexity password cracking has been the cause of serious research and discussion in the field of cyber security. In this research, it is highly relevant to carry out modeling and synthesis of authentication in effective data storage and network security in cyberspace. In this work, the authentication procedure, which is one of the main components of cyber security in cyberspace, is modeled on the basis of a functional table. The attributes used in the cyber system are grouped, and research, analysis and experiments are conducted with models for the grouped parts. The purpose of this study is to show that safety increases with the number of attributes and decreases with the chance of repeating the wrong sequence of symptoms.